Understanding the Unique Psychological Demands of Competitive Collegiate Rowing: A Guide for Practitioners. Issue 1 (2nd March 2021) - Rich, Jason; Pottratz, Suzanne T.; Leaf, Beau
Abstract: As awareness of the impact of the mental side of competition grows, rowing programs are increasingly seeking out the services of mental performance consultants and sport psychologists. Currently, due to limited exposure and experience in the sport of rowing, there is a gap in knowledge of the specific constraints of the sport. The purpose of this article is to outline the unique psychological demands of collegiate rowing, and to serve as a starting point for practitioners seeking to consult within the sport. Guidelines and recommendations are provided for how to implement mental skills training with collegiate rowers.